HUBUNGAN ANTARA SELF EFFICACY DENGAN PRESTASI BELAJAR MAHASISWA FAKULTAS HUKUM UNIVERSITAS KATOLIK SANTO THOMAS SUMATERA UTARA - Dwi Nursiti; Laksana Tobing; Sri Ramadhan; Rutmana Silalahi (Psikologi Universitas Sari Mutiara Indonesia, 2019)
This study aims to determine the relationship between self efficacy and student achievement in the Faculty of Law of the Santo Thomas Catholic University of North Sumatra. This type of research is a quantitative study with 53 subjects of students, who were chosen by saturated sampling, from the data collected using self efficacy scale and document data of learning achievement index results. The results of this study are known to have a validity of 0,306-0,637 and a reliability value of 0,941 and the Kolmogorov smirnov value is 0,888 (p> 0,05), the Iinear value is 0,403 (p> 0,05). This means the results of linear research. The data were analyzed by using the Product Moment correlation analysis technique and the result of r = 0,103 with a significance of 0,464 (p> 0,05), this states that